The Civilian Legacy of the Roman Army - Loschiavo, Luca, (History of Warfare ;, 2024)
The Roman army represented an important social and organizational reference model for the Romano-Barbarian societies, which progressively replaced the Western Empire in the transition from Late Antiquity to Early Middle Ages. The great flexibility of the decision-making and organizational solutions used by the Roman army allowed the 'new lords' to readapt them and thus maintain power in early medieval Europe for a long time. From a perspective ranging from political, social and economic history to law, anthropology, and linguistic, this book demonstrates how interesting and fruitful the investigation of this specific cultural imprint can be in order to gain a better understanding of the origins of the civilization that arouse after the fall of the Roman world. Contributors are Francesco Borri, Fabio Botta, Francesco Castagnino, Stefan Esders, Carla Falluomin, Stefano Gasparri, Wolfgang Haubrichs, Soazick Kerneis, Luca Loschiavo, Valerio Marotta, Esperanza Osaba, Walter Pohl, Jean-Pierre Poly, Pierfrancesco Porena, Iolanda Ruggiero, Andrea Trisciuoglio, Andrea A. Verardi, and Ian Wood.